A Corpus Linguistics Approach to the Representation of Western Religious Beliefs in Ten Series of Chinese University English Language Teaching Textbooks - Liu, Yanhong; Zhang, Lawrence Jun; Yang, Li (Frontiers in Psychology, 2022)
The early Sino-Western contact was through the way that religion and language interact to produce language contact, however, this contact is relatively little explored to date (Spolsky, 2003). Particularly, in the realm of English language materials, there is a paucity of research on Western religions in ELT textbooks. By applying the synergy of theoretical framework Critical Discourse Analysis and corpus linguistics approach, this paper critically investigate into the significant semantic domains in ten English language textbook series that are officially approved and widely used for most Chinese universities. The findings suggest that various Western religious beliefs, the highly unusual topics in previous Chinese ELT textbooks, are demonstrated in the textbook corpus. The results also show that when presenting the views and attitudes toward Western religious beliefs, an eclectic approach has been adopted in terms of material selection. Surprisingly, positive semantic prosody surrounding the concept of religion captured and no consistent negative authorial stance toward religion is evident though atheism is in the center of Chinese intellectuals’ tradition and CCP. The empirical findings in this study provide a new understanding of Chinese foreign language textbooks in the new era and add to the literature on the study of ELT textbooks and its development worldwide.